WOMEN MIGRANT WORKERS AND SOCIAL PROTECTION SYSTEMS IN THE PHILIPPINES - Purwo Purwowi Wibowo (SAMPURASUN, 2017)
Women migrant workers often face a variety of problems in the workplace, for example violence, sexual abuse, rape, extortion, and so on. Social protection systems for women migrant workers in other countries are very important. In the Philippines, there are two social protection systems to improve social welfare for vulnerable populations. Two models of social protection called the health care system and social health insurance. Both social protection systems can be managed, as based on: (1) culture value, (2) to be funded by the financial institutions, (3) implemented freely, (4) the scheme is combined with the national health insurance system, (5) able to create a high quality service. The conditions of women migrant workers are more vulnerable than male workers. So, the social protection for women migrant workers is urgent and need policies to protect them. The Government of the Philippines emphasizes the problems related to the obligation of women migrant workers to have right information and guidance before they leave the country in order to minimize social problems. Finally, social protection, not only in the Philippines, but also cooperation among countries to ptotect women migrant workers by making policy of social protection from local, national, regional, and international level. Keywords: Migrant Worker, Social Protection in Philippines, Health Care System, Social Health Insurance